Decreasing but still high levels of halogenated flame retardants in wetland birds in central Spain. (August 2019) - Eljarrat, E.; Aznar-Alemany, Ò.; Sala, B.; Frías, Ó.; Blanco, G.
Abstract: The occurrence of classical and emerging halogenated flame retardants in bird samples collected between 2010–17 from the Castrejón reservoir (central Spain) was studied. Different wetland bird samples were analysed, including unhatched bird eggs and liver of dead nestlings. Polybrominated diphenylethers (PBDEs) were detected in all the samples at high concentration values, with levels up to 5167 ng/g lw. Dechloranes were found in 78% of analysed samples, but at lower concentration levels, between not detected (nd) and 2153 ng/g lw. The time trend evaluation over the sampling period showed an approximately 50% decline in mean concentrations of PBDEs. However, the most recent data for PBDEs (2016–17) still indicate that, in some cases, and based on reported LOECs, wetland birds were exposed to PBDE concentrations that are associated with possible ecological hazards. Highlights: PBDEs were detected at high concentrations, with levels up to 5167 ng/g lw. Dechloranes were found in 78% of samples, at concentrations up to 2153 ng/g lw. Time trend evaluation for PBDEs along 2010–2017 showed a level decline. Based on reported LOECs, birds were still exposed to PBDEs associated to ecological hazards.